PENGEMBANGAN BASIS DATA PROGRAM KELUARGA BERENCANA TINGKAT PUSKESMAS - Sujud Mardi Raharja; Santi Martini (Universitas Jember, 2015)
Family planning (FP) is a program that can reduce the rate of infant and maternal mortality. The purpose of this study was to develop a database model for family planning programs in Primary Health Care (Puskesmas). The scope of the data base development includes the service planning program at Puskesmas working area. This type of research was an action research. Subjects in this study were the management of family planning programs in the province, district, health centers and family planning implementer program in the village. The result of analysis system for recording and reporting of family planning programs in Puskesmas were found some problems: unstandardized format registers, duplicate records, manual storage of data, unautomated processing of the reports, and limited produced of information. The result of this study was a prototype of database family planning programs in the health center based on the information needs of managers of family planning programs. The developed database program for family planning at the health center can be generated based on the information needed by family planning programs managers therefore it can be utilized to monitor and evaluate the performance of the family planning program in the health center.